Attitudes of first-year nursing students at Tallinn Health University of Applied Sciences towards violence against women - Marika Merits; Mare Tupits; Irma Nool (Proceedings of the Estonian Academy of Sciences)
Violence against women (VAW) is defined by the United Nations as any gender-based violence that causes mental, physical, or economic harm and restricts freedom. The topic has not been studied before in the context of the nursing curriculum in Estonia. The objective of the study was to investigate the attitude of first-year nursing students towards VAW and provide input to improve the quality of the nursing curriculum content when addressing the topic of violence. The study was conducted using a cross-sectional method. The study population consisted of the first-year nursing students at Tallinn Health Care College (now Tallinn Health University of Applied Sciences) during the period of 2022â2023. The online survey was distributed to 120 first-year nursing students of the college. The results of the study show that 96.00% of students have a generally negative attitude towards VAW, but this attitude contains certain limitations. Respondents know about the types of violence and have personal experiences with violence, but their knowledge of the impact of violence on womenâs health is limited. There are some negative beliefs and behavioural tendencies that indicate that less than half of the respondents would know how to help a woman as a victim. Based on the above, it is possible to gain input for addressing violence-related issues in the nursing curriculum. Violence-related topics should be included in the nursing curriculum, along with the development of practical skills that help shape the right attitudes.